A survey of viral and phytoplasmal diseases of trees from nanded district - Gawate, A B; Papdiwal, P B (International Multidisciplinary Research Journal, 2011)
During the survey of viral and phytoplasmal diseases of trees of Nanded district, 5 diseases were observed. Mejority of them were observed on fruit trees. The diseases observed were Leaf curl, Ring spot and Mosaic of papaya; Tristeza disease of Citrus aurantium and Witche’s Broom disease of Zizyphus mauritiana. A brief report of this investigation is presented in this paper.